MODEL PEMERINGKATAN RISK DAN RETURN SAHAM BLUE CHIP YANG TERDAFTAR PADA LQ 45 BURSA EFEK INDONESIA - SOEBRATI, NI WAYAN; RAHMIYATI, NEKKY; RATNAWATI, TRI (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2019)
ABSTRACTThe purpose of this study is to produce a method of determining blue chip shares and a risk & return rating model for blue chip stocks that are listed on the Indonesia Stock Exchange LQ45 shares. This study uses a sample of LQ45 stocks listed during the 2013-2017 period. According to the method prescribed by the researcher to determine which blue chip categories produce 8 stocks that are included in the criteria of blue chip shares. Calculation of risk & return is calculated based on monthly data for the period 2013-2017 using the Single Index Model and using the Microsoft Excel program. The market index used in this study is the closing price index of LQ45. This study uses the 2013-2017 LQ45 closing price data to calculate the return market. The data sources used in this study are secondary data, data collection techniques carried out by purposive sampling method. Based on the calculation of risk & return from the 8 selected stocks, the return rate for BBNI was 26.69%, BBCA 20.33%, BSDE 14.42%, BBRI 9.47%, BMRI 8.38%, TLKM 7.63 %, ASII 6.68%, MNCN 2.81% while the risk of BBCA shares is 1.66%, BSDE 2.5%, ASII 3.02%, MNCN 3.48%,BMRI 4.05%, BBNI 6.42%, BBRI 7.88%, TLKM 8.73 %. BBNI, BBCA, BSDE and BBRI shares have returns above the market return of 8.70%. A return is a promising return, because the return is above the market return, while from the risk assumption it is known that the market risk of 1.76% is the risk borne by the investor. All stocks have a positive return except MNCN shares that have a negative return. Stocks that have a positive expected return are stocks that are worthy of being an alternative investment. Stock ranking based on the highest return and lowest risk. The results of the study show that the stock that provides the highest comparison of the lowest return and risk is BBCA, besides BBCA also has a return on market returns and risks under market risk. Keywords: Risk, Return, LQ45, Blue Chip stock, single index model